Effects of migration distance and sex on stopover timing and refueling by Wilson's Warblers. Issue 2 (2nd May 2018) - Hays, Quentin R.; Morbey, Yolanda E.; Hobson, Keith A.; Lyons, James E.; Guglielmo, Christopher G.
Abstract: Migration distance and sex are integral to avian migration strategies, yet these intrinsic factors are understudied with respect to their effects on stopover ecology and behavior. We investigated how individual variation in migration distance and sex affected body condition, refueling performance, and stopover durations of Wilson's Warblers ( Cardellina pusilla ) during spring and fall 2006 at a stopover site in southern Arizona. Migration distance of individuals was inferred using the hydrogen stable isotope ratio of feathers (δ 2 Hf ) as an index of breeding latitude, refueling rate was assessed using plasma triglyceride and β‐OH‐butyrate, and minimum length of stay was estimated by re‐sighting color‐banded birds. In the spring, migration distance and sex were strong determinants of the timing of migration by Wilson's Warblers, with males and shorter‐distance migrants passing through the site earlier than females and longer‐distance migrants. Later‐arriving migrants also had higher fat scores and refueling rates. However, neither migration distance nor sex independently affected body condition (fat score or size‐corrected mass), refueling rate, or minimum length of stay. In a smaller sample of fall migrants, we found that longer‐distance migrants and males had higher refueling rates than shorter‐distance migrants and females. Our results show that differences in migration distance can, under some circumstances, affect how birds use stopover sites. Stable isotope analysis and other methods can provide information on migration distance, and should be integrated with measurements of timing, fuel stores, refueling performance, and departure behavior to gain a deeper understanding of bird migration.